2024
DOI: 10.3390/genes15020229
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Genes and Pathways Linked to the Temperament Trait in Sheep

Estefanía Romaniuk,
Brenda Vera,
Pablo Peraza
et al.

Abstract: Temperament can be defined as the emotional variability among animals of the same species in response to the same stimulus, grouping animals by their reactivity as nervous, intermediate, or calm. Our goal was to identify genomic regions with the temperament phenotype measured by the Isolation Box Test (IBT) by single-step genome-wide association studies (ssGWAS). The database consisted of 4317 animals with temperament records, and 1697 genotyped animals with 38,268 effective Single Nucleotide Polymorphism (SNP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…On the other hand, LAP3 also contributes to growth, milk production and feed efficiency traits in sheep [55]. The GPRIN3 gene has been linked to prolificacy, litter size [56] and temperament in sheep [57].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, LAP3 also contributes to growth, milk production and feed efficiency traits in sheep [55]. The GPRIN3 gene has been linked to prolificacy, litter size [56] and temperament in sheep [57].…”
Section: Discussionmentioning
confidence: 99%
“…It is strongly related to dry matter intake, average daily gain, birth weight and milk fat yield in cattle [62]. However, earlier research indicated that GRID2 plays a role in the sexual maturity of Simmental cattle, the temperament trait of sheep and the litter size of goat [63][64][65]. On BOE, key genes associated with traits such as fertility (BIRC6), disease resistance (PDCD1LG2, SVIL), cold tolerance (PRDM16), bone development (ACYP2), meat production (CFAP74) and growth performance (SMG6) were discovered.…”
Section: Functional Enrichment Analysismentioning
confidence: 99%